Corruption and international trade: a comprehensive analysis with gravity. Issue 79 (2nd September 2019) - Gil-Pareja, Salvador; Llorca-Vivero, Rafael; Martínez-Serrano, José Antonio
Abstract : Purpose: The purpose of this paper is to analyze the impact of corruption on trade. Design/methodology/approach: The authors estimate gravity equations with the last econometric advances on a wide sample of countries and years using three different measures of corruption. Two of them belong to the so-called perception-based indexes and the third is derived from a structural model that takes into account the causes and indicators of corruption across countries. Findings: A negative effect of corruption on trade appears with perceptions, but it is not widespread. However, the authors find sensible evidence of the "grease the wheels" view with the structural index if low and middle income countries are implicated. Additionally, when using this measure, differences in corruption levels negatively impact trade. Both results are in line with expectations. Originality/value: Moreover, membership in regional trade agreements does not seem to significantly alter these results.